On the Sr(1−x)Ba(x)FeO(2)F Oxyfluoride Perovskites: Structure and Magnetism from Neutron Diffraction and Mössbauer Spectroscopy - García-Ramos, Crisanto A. (Materials (Basel), 2016)
Four oxyfluorides of the title series (x = 0.00, 0.25, 0.50, 0.75) have been stabilized by topotactic treatment of perovskite precursors Sr(1−x)Ba(x)FeO(3−δ) prepared by soft-chemistry procedures, yielding reactive materials that can easily incorporate a substantial amount of F atoms at moderate temperatures, thus avoiding the stabilization of competitive SrF(2) and BaF(2) parasitic phases. XRD and Neutron Powder Diffraction (NPD) measurements assess the phase purity and yield distinct features concerning the unit cell parameters’ variation, the Sr and Ba distribution, the stoichiometry of the anionic sublattice and the anisotropic displacement factors for O and F atoms. The four oxyfluorides are confirmed to be cubic in all of the compositional range, the unit cell parameters displaying Vergard’s law. All of the samples are magnetically ordered above room temperature; the magnetic structure is always G-type antiferromagnetic, as shown from NPD data. The ordered magnetic moments are substantially high, around 3.5 μ(B), even at room temperature (RT). Temperature-dependent Mössbauer data allow identifying Fe(3+) in all of the samples, thus confirming the Sr(1−x)Ba(x)FeO(2)F stoichiometry. The fit of the magnetic hyperfine field vs. temperature curve yields magnetic ordering T(N) temperatures between 740 K (x = 0.00) and 683 K (x = 0.75). These temperatures are substantially higher than those reported before for some of the samples, assessing for stronger Fe-Fe superexchange interactions for these specimens prepared by fluorination of citrate precursors in mild conditions.